Revealing the Subsurface Yellow Sea Cold Water Mass from Satellite Data Associated with Typhoon Muifa. Issue 10 (24th October 2019) - Yang, Yang; Li, Kuiping; Du, Jianting; Liu, Yanliang; Liu, Lin; Wang, Huiwu; Yu, Weidong
Abstract: A significant sea surface temperature (SST) drop was clearly identified to be confined exactly over the Yellow Sea Cold Water Mass (YSCWM) from satellite‐derived SSTs during Typhoon Muifa's passage over the Yellow Sea (YS) in early August 2011. With a simple one‐dimensional mixed‐layer model (Price‐Weller‐Pinkel [PWP]), the mixed‐layer heat budget diagnosis concluded that the entrainment term, rather than the surface heat flux term that usually dominates over the open ocean, was the dominant process for the significant SST cooling over the YSCWM. The PWP‐based experiments were conducted to set up one lookup table including the SST drop, wind speed, and subsurface temperature gradient, from which the YSCWM's intensity (represented by the subsurface temperature gradient) can be easily found with the satellite wind and SST measurements during the typhoon passage over the YS. This YSCWM‐anchored significant SST drop provides a promising possibility to detect the YSCWM intensity and extent, which have generally been poorly sampled to date. Plain Language Summary: The Yellow Sea Cold Water Mass (YSCWM) not only dominates the hydrographic features but also has significant effects on the marine ecosystem in the Yellow Sea (YS). Currently, the in situ measurements of the YSCWM are still too sparse to fully document and understand the complexity of the YSCWM. It was shown here that the SST cooling associated with Typhoon Muifa in August 2011 exhibits a unique spatial pattern that well resembles the spatial extent of the YSCWM. The detailed analysis concluded that this YSCWM‐anchored SST drop is due to the strong subsurface temperature gradient associated with the YSCWM. This finding raises the possibility of detecting the scope and intensity of the YSCWM using a lookup table that is established from a series of mixed‐layer model experiments. Key Points: The pattern of the SST drop over the Yellow Sea during the passage of Typhoon Muifa in August 2011 resembles that of the YSCWM It is found that the sharp subsurface temperature gradient accounts for the YSCWM‐anchored SST cooling A promising possibility to detect the YSCWM from satellite data is proposed